Experiences and Educational Needs of Hospital Staff Providing Care to Tracheostomy-Dependent Pediatric Patients - Kathryn L. Palumbo; Desirae Smith; Adrianne Frankel; Laine DiNoto; Taylor Wheaton; Kimberly Buholtz; Rita Dadiz (Children)
Objective: To assess the experience and educational needs of hospital staff who care for pediatric patients with tracheostomies. Study Design: Staff were surveyed and participated in semi-structured, facilitated focus groups regarding their experiences caring for children with tracheostomies and their educational needs. Survey data were analyzed using descriptive statistics and Kruskal–Wallis nonparametric tests. Focus groups were transcribed verbatim and coded for thematic analysis. Results: Pediatric advanced practice providers, nurses, physicians, and respiratory therapists (152/353, 43%) completed the survey. Within the last year, 76% of staff had worked with a tracheostomy-dependent child. However, up to 59% of staff had not performed at least one tracheostomy skill (e.g., tracheostomy site assessment, tube change, etc.). Staff reported the least confidence in changing tracheostomy tubes and using home ventilators and rated these skills as most important for additional education. Forty-three staff members participated in 1 of 10 focus groups. Three themes were identified: building staff competencies in tracheostomy care, promoting the caregiver development of tracheostomy skills, and building caregiver preparedness for home life. Staff emphasized the need for participating in emergency simulations and developing their skills to better prepare caregivers for home life. They indicated a need to streamline the discharge process, gain knowledge of community resources, and develop a standardized team to provide discharge teaching. Conclusions: Hospital staff responsible for providing care to tracheostomy-dependent pediatric patients had limited opportunities to learn and maintain their skills. Survey and focus group findings can guide development of continuing education to optimize the care of tracheostomy-dependent children.